(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Shakespeare’s women characters have regularly pulled inthe consideration of the authorities over the time. In this paper we presentabout the questionable parts of the women part in Shakespeare’s comedies wereespecially evoked by twentieth century experts. Even though the aforementionedwomen characters have been seriously examined and investigated, certaincontentions and contradictions over the understanding of the women part wereregularly left unresolved.